Experts and Cultural Narcissism: Relations in the Early 21st Century - Andrzej Klimczuk (LAP Lambert Academic Publishing; ZBW - Leibniz Information Centre for Economics, 2012)
Local and global dependencies and interactions between individuals, groups and institutions are becoming increasingly opaque and risky. This is due to increased importance of highly complex abstract systems created and supported in order to maintain of transport, communications, finance, energy, media, security infrastructure, as well as social and cultural institutions. These systems require the knowledge and skills of experts. Professionals that not only satisfy identified needs, but also create new thereby contribute the development of cultural narcissism phenomenon. The aim of the book is to discuss relations of experts and mass narcissism, on the background of shaping the knowledge societies and knowledge-based economies, and moreover their transformations towards the societies and economies based on creativity and wisdom. Undertaken analysis is contribute to sociology of expertise and intervention by indicating four selected contemporary issues: dilemmas of the knowledge society development; selection between trust substitutes and its reconstruction methods; transformations of social stratification; and the choice of pathways to socio-economic development.
Keywords: R10; Z13; 330; regional policy; social capital; policymaking